Health Monitoring Systems for Pregnant Women: Challenges and Issues (Medico Legal Update, 2021)
It is important for all pregnant women throughout their gestational period to be able to access information,services and care by having direct communication with their doctors or their healthcare provider or theirrelatives. With the proliferation of mobile devices and the internet it has become very easy to get access tosuch information in a quick and efficient manner. There are also several awareness programs which teachabout the right kind of physical activity and food to be followed by such pregnant women. Having accessto such information helps these women identify and prevent any pregnancy related complications or riskswhich could lead to issues such as still-birth, pre term labor etc. Women who do not use this informationwisely are likely to be putting their lives as well as the lives of their babies at risk. The main objective ofthis paper is to analyse various compound reasons pregnancy related issues and the technologies availableto solve such issues.